2015
DOI: 10.1371/journal.pone.0135524
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deep Brain Stimulation on the Lived Experience of Obsessive-Compulsive Disorder Patients: In-Depth Interviews with 18 Patients

Abstract: Deep Brain Stimulation (DBS) is a relatively new, experimental treatment for patients suffering from treatment-refractory Obsessive Compulsive Disorder (OCD). The effects of treatment are typically assessed with psychopathological scales that measure the amount of symptoms. However, clinical experience indicates that the effects of DBS are not limited to symptoms only: patients for instance report changes in perception, feeling stronger and more confident, and doing things unreflectively. Our aim is to get a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 63 publications
11
89
0
Order By: Relevance
“…It's like plastic surgery, you might change your nose but how you feel about yourself is still the same^ [19]. Elsewhere, de Haan et al [14], after interviewing 18 OCD patients implanted with DBS, concluded that: BApart from the previously documented improvement of mood, diminishment of anxiety, and increase of impulsivity, we also found changes such as an increase in trust, self-reliance, and self-confidence, a more unreflective mode of engagement, and a more careless stance on things^ [14]. Our review found that when the putative effects of DBS on…”
Section: ) Conclusion Of Studies Not Matching Neuroethics Claimsmentioning
confidence: 99%
“…It's like plastic surgery, you might change your nose but how you feel about yourself is still the same^ [19]. Elsewhere, de Haan et al [14], after interviewing 18 OCD patients implanted with DBS, concluded that: BApart from the previously documented improvement of mood, diminishment of anxiety, and increase of impulsivity, we also found changes such as an increase in trust, self-reliance, and self-confidence, a more unreflective mode of engagement, and a more careless stance on things^ [14]. Our review found that when the putative effects of DBS on…”
Section: ) Conclusion Of Studies Not Matching Neuroethics Claimsmentioning
confidence: 99%
“…Previous research indicates that in general changes—both for better and for worse—may be more readily noticed by close relatives [13, 20, 26]. The assessments of relatives are not decisive either, though, for they may not have known the patient without OCD.…”
Section: Preliminary Considerationsmentioning
confidence: 99%
“…For example, the possibility of meeting up with a friend now or in the future is experienced as lacking affective allure. In other words, depression results in the deactivation of the soliciting field of relevant affordances that normally drives individuals towards an optimal grip on their situation(Rietveld, De Haan, and Denys 2013;De Haan et al 2013;De Haan et al 2015). On this basis it can be said that depression entails a breakdown of a key aspect of everyday skillful action.…”
mentioning
confidence: 99%